Efeito do ácido alfa-lipóico sobre parâmetros hematológicos e metabolismo do ferro em hipertensos - Mendes, Paula Renata Florêncio (2013)
The etiology of systemic arterial hypertension (SAH) has been linked to oxidative stress and excess or deficiency of iron, which can also cause disturbance in the antioxidant system. The α-lipoic acid (ALA) is used as a treatment to reduce oxidative damage in SAH, but there are no in vivo studies reporting the effect of its mechanism of action on iron metabolism. AIM: To study the effect of alpha-lipoic acid as antioxidant supplement used in the treatment of various noncommunicable chronic diseases and its new applications and evaluate the effect of ALA on blood cell count and iron kinetics in hypertensive patients with or without anemia, comparing the results between treatment group and control group. METHOD: Double-blind, randomized, placebo-controlled trial conducted from October/2012 to January/2013. Participants were 60 hypertensive patients with or without Diabetes Mellitus and distributed into treatment group (n = 32), receiving 600 mg / day of ALA for twelve weeks and control group (n = 28), receiving placebo for the same period. Blood cell count, serum iron, ferritin, Latent Iron-Binding Capacity (LIBC), Total Iron-Binding Capacity (TIBC), Transferrin Saturation Index (TSI) and transferrin were assessed before and after intervention. Intervention was prospectively evaluated by comparing results within and between groups using the paired Student t-test and ANOVA. The standardized coefficient of Cohen (d) was used to estimate the clinical effect adopting a significance level of 5%. RESULTS: The therapeutic action of ALA in the treatment of various diseases with oxidative potential has been proven through clinical trials, but there is still need for further studies to prove its effectiveness in relation to its various sites of action. The majority of patients were older than 60 years, and 75.0% were female. Only 3.3% of the sample showed changes in blood count compatible with Iron Deficiency Anemia. After intervention, the blood cell count in the treatment group showed a statistically significant increase in the number of neutrophils and reduction in the number of monocytes (p <0.05), but no significant changes were observed in the red series. A statistically significant reduction (p <0.05) in the serum iron levels and TSI when compared to the placebo group was observed. CONCLUSIONS: Most studies have demonstrated the role of lipoic acid in reducing the oxidative stress, but still further in vivo clinical trials are needed to investigate its therapeutic potential in the prevention of damages from noncommunicable chronic diseases. It was observed that the oral administration of ALA showed statistically significant changes in leukocyte counts and iron metabolism and for this reason its use as antioxidant supplement should be monitored and / or reevaluated in order to avoid complications in iron metabolism and thus prevent the occurrence of iron deficiency anemia.